Postcards from the edge of SoTL: A view from faculty development - Hodges, Linda C. (Teaching and Learning Inquiry, 2013)
As a past SoTL scholar turned faculty developer, I have come to realize that SoTL is a mindset: one of questioning old assumptions about what teaching entails and how our students learn, gathering and examining evidence of the effects of our approaches, and reflecting on and sharing insights gained. This perspective changed my own teaching. Now it informs each consultation I have with faculty, upending much of what faculty traditionally believe about teaching on intellectual, social, and personal levels. By adjusting the frame through which we view teaching, SoTL has revelatory power in catalyzing change. In this article, I discuss how key precepts of SoTL enhance the day-to-day work of faculty development. Specifically, through SoTL, faculty realize that course design is an intellectual endeavor, that students are complex individuals from whom they can learn, and that teaching is an ongoing transformational journey to be shared.